Routing in heterogenen OpenFlow Netzwerken - Wallaschek, Felix

Arbeitskräftebedarf bei hoher Arbeitslosigkeit: ein ökonomisches Zuwanderungskonzept für Deutschland - Zimmermann, Klaus F; Bauer, Thomas K; Bonin, Holger; Fahr, Rene; Hinte, Holger

The impact of risk perception and risk attitudes on corrupt behavior: Evidence from a petty corruption experiment - Mir Djawadi, Behnud; Fahr, Rene

The impact of tax knowledge and budget spending influence on tax compliance - Djawadi, Behnud Mir; Fahr, Rene

Ressource-Optimized Deployment of Multi-Tier Applications - The Data Rate-Constrained Case - Robbert, Christoph

Reputationssysteme und Gerichtsverfahren als Wekzeuge zur Sicherstellung von Qualitätsstandards in Transaktionen - Terentjew, Artjom

Reengineering of Component-Based Software Systems in the Presence of Design Deficiencies - von Detten, Markus
The maintenance of component-based software systems requires up-to-date models of their concrete architecture, i.e. the architecture that is realised in the source code. These models help in systematically planning, analysing and executing typical reengineering activities. Often no or only outdated architectural models of such systems exist. Therefore, various reverse engineering methods have been developed which try to recover a system's components, subsystems and connectors. However, these reverse engineering methods are severely impacted by design deciencies in the system's code base, especially violations of the component encapsulation. As long as design deciencies are not considered in the reverse engineering process, they reduce the quality of the recovered component structures. Despite this impact of design deciencies, no existing architecture reconstruction approach explicitly integrates a systematic deciency detection and removal into the recovery process. Therefore, I have developed Archimetrix. Archimetrix is a tool-supported architecture reconstruction process. It enhances a clustering-based architecture recovery approach with an extensible, pattern-based deciency detection. After the detection of deciencies, Archimetrix supports the software architect in removing the de ciencies and provides the means to preview the architectural consequences of such a removal. I also provide a process to identify and formalise additional deciencies. I validated the approach on three case studies which show that Archimetrix is able to identify relevant deciencies and that the removal of these deciencies leads to an increased quality of the recovered architectures, i.e. they are closer to the corresponding conceptual architectures.

Reducing Nondeterminism in Automated Service Composition - Mohr, Felix; Lettmann, Theodor; Kleine Büning, Hans (Proceedings of the 6th International Conference on Service Oriented Computing and Applications (SOCA))
Automated service composition has been studied as a subject of state based planning for a decade. A great deal of service composition tasks can only be solved if concrete output values of the services are considered in the composition process. However, the fact that those values are not known before runtime leads to nondeterministic planning problems, which have proven to be notoriously difficult in practical automated service composition applications. Even though this problem is frequently recognized, it has still received remarkably few attention and remains unsolved.This paper shows how nondeterminism in automated service composition can be reduced. We introduce context rules as a means to derive semantic knowledge from output values of services. These rules enable us to replace nondeterministic composition operations by less nondeterministic or even completely deterministic ones. We show the validity of our solutions not only theoretically but also have evaluated them practically through implementation.

Reactive Planar Spanner Construction in Wireless Ad Hoc and Sensor Networks - Benter, Markus; Neumann, Florentin; Frey, Hannes (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Within reactive topology control, a node determines its adjacent edges of a network subgraph without prior knowledge of its neighborhood. The goal is to construct a local view on a topology which provides certain desired properties such as planarity. During algorithm execution, a node, in general, is not allowed to determine all its neighbors of the network graph. There are well-known reactive algorithms for computing planar subgraphs. However, the subgraphs obtained do not have constant Euclidean spanning ratio. This means that routing along these subgraphs may result in potentially long detours. So far, it has been unknown if planar spanners can be constructed reactively. In this work, we show that at least under the unit disk network model, this is indeed possible, by proposing an algorithm for reactive construction of the partial Delaunay triangulation, which recently turned out to be a spanner. Furthermore, we show that our algorithm is message-optimal as a node will only exchange messages with nodes that are also neighbors in the spanner. The algorithm’s presentation is complemented by a rigorous proof of correctness.

Programs from Proofs – A PCC Alternative - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 25th International Conference on Computer Aided Verification (CAV))
Proof-carrying code approaches aim at safe execution of untrusted code by having the code producer attach a safety proof to the code which the code consumer only has to validate. Depending on the type of safety property, proofs can however become quite large and their validation - though faster than their construction - still time consuming. In this paper we introduce a new concept for safe execution of untrusted code. It keeps the idea of putting the time consuming part of proving on the side of the code producer, however, attaches no proofs to code anymore but instead uses the proof to transform the program into an equivalent but more eﬃciently veriﬁable program. Code consumers thus still do proving themselves, however, on a computationally inexpensive level only. Experimental results show that the proof eﬀort can be reduced by several orders of magnitude, both with respect to time and space.

Profitable Scheduling on Multiple Speed-Scalable Processors - Kling, Peter; Pietrzyk, Peter (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present a new online algorithm for profit-oriented scheduling on multiple speed-scalable processors.Moreover, we provide a tight analysis of the algorithm's competitiveness.Our results generalize and improve upon work by \citet{Chan:2010}, which considers a single speed-scalable processor.Using significantly different techniques, we can not only extend their model to multiprocessors but also prove an enhanced and tight competitive ratio for our algorithm.In our scheduling problem, jobs arrive over time and are preemptable.They have different workloads, values, and deadlines.The scheduler may decide not to finish a job but instead to suffer a loss equaling the job's value.However, to process a job's workload until its deadline the scheduler must invest a certain amount of energy.The cost of a schedule is the sum of lost values and invested energy.In order to finish a job the scheduler has to determine which processors to use and set their speeds accordingly.A processor's energy consumption is power $\Power{s}$ integrated over time, where $\Power{s}=s^{α}$ is the power consumption when running at speed $s$.Since we consider the online variant of the problem, the scheduler has no knowledge about future jobs.This problem was introduced by~\citet{Chan:2010} for the case of a single processor.They presented an online algorithm which is $α^{α}+2eα$-competitive.We provide an online algorithm for the case of multiple processors with an improved competitive ratio of $α^{α}$.

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Proceedings)

The after effects of strikes on team collaboration-experimental evidence - Thommes, Kirsten; Akkerman, Agnes; Vyrastekova, Jana (Academy of Management Proceedings)

Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im JUngtätervollzug

Didaktik beruflicher Bildung - Kremer, H.-Hugo; Fischer, M.; Tramm, T. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Standardization, professionalization and the measurements

Evidences of defect contribution in magnetically ordered Sm-implanted GaN - Lo, Fang-Yuh; Guo, Jhong-Yu; Huang, Cheng-De; Chou, Kai-Chieh; Liu, Hsiang-Lin; Ney, Verena; Ney, Andreas; Chern, Ming-Yau; Shvarkov, Stepan; Reuter, Dirk; Wieck, Andreas D.; Pezzagna, Sébastien; et al. (Current Applied Physics)

Combined influence of Coulomb interaction and polarons on the carrier dynamics in InGaAs quantum dots - Steinhoff, A.; Kurtze, H.; Gartner, P.; Florian, M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Picosecond real-space imaging of electron spin diffusion in GaAs - Henn, T.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)